Homestay industry – drivers and challenges in the State of Johor, Malaysia - Md. Yassin, Azlina; Arif, Norjariah; Perumal Naidu, Jeya Lechumy (2017)
The growth in Malaysiantourism industry has led to high demand for homestayas a tourism product, albeit indirectly. With thatgrowth, it has been acknowledged that homestay accommodation business plays a significant role in aiding the success of the tourism industry in Malaysia.There arealready a large number of registered homestay entrepreneurs and the number is growing. The main aim of this paper isto examinethe factors that contribute to thegrowth of homestay industry in Johor.The conceptis introduced while the drivers and barriers to the business are also discussed in this paper. A literature review was earlier undertaken on homestayentrepreneurships around the worldto offer some measure of comparison.